The Realization of Strong Diplomacy Towards Indonesia Golden 2045 in the North Natuna Sea Conflict using Force Planning Approach - Daniela, Nurfaizah Azhari; Alam, Tasdik Mustika; Prakoso, Lukman Yudho; Patmi, Sri (Formosa Journal of Applied Sciences, 2024)
The South China Sea has become a battleground for major powers' hegemonic struggles. Indonesia, due to China's claim over the North Natuna Sea, is involved in the conflict, utilizing a force planning approach. The historical and strategic values have made the South China Sea a region of complex conflicts involving global hegemony. The research used a qualitative descriptive method. Indonesia's response includes capability-based planning through law enforcement, scenario-based planning with naval base construction, and threats-based planning through military buildup in the North Natuna Sea. This escalating conflict in the South China Sea is pulling Indonesia further into the vortex, necessitating strategic steps through a force planning approach to protect its sovereignty and interests.